Isolation and chemical characterization of 2-hydroxybenzoylglycine as a drug binding inhibitor in uremia. - Lichtenwalner, D M (1983)
An organic compound that inhibits drug binding in uremia has been isolated from the sera of chronic renal failure patients, and its chemical structure has been determined. Addition of the compound to normal human sera in vitro resulted in drug binding defects similar to those seen in uremia. The purification of this substance was accomplished by n-butyl chloride extraction of acidified (pH 3.0) uremic sera followed by column chromatography, thin-layer chromatography, and paper electrophoresis. From analytical studies including ultraviolet and fluorescence spectroscopy, gas chromatography, chemical ionization and electron impact mass spectrometry, and proton nuclear magnetic resonance spectroscopy, the chemical structure of the uremic binding inhibitor was deduced to be 2-hydroxybenzoylglycine. This confirms the hypothesis that the drug binding defect in uremia is due to the accumulation of endogenous metabolic products rather than an intrinsic structural defect in albumin.